Academics' conceptualisations of the research-teaching nexus in a research-intensive Irish university: A dynamic framework for growth & development. (April 2019) - Brennan, Lorraine; Cusack, Tara; Delahunt, Eamonn; Kuznesof, Sharron; Donnelly, Suzanne
Abstract: The interdependent relationship between research and teaching is at the heart of research-intensive universities. In the present study, an initial electronic quantitative survey was undertaken following which, we performed 28 in-depth, semi-structured interviews amongst a cross-section of faculty in a research intensive Irish university to capture how faculty conceptualise the relationship between research and teaching. Our qualitative analysis revealed a dynamic framework with three interacting phases: 1) teaching is enhanced by research 2) learning research skills and competencies; and 3) student engagement with research practice. These themes contribute to the development of the student as a researcher and the implicit vision of the research-intensive university as a 'community of scholars' where teaching enhances research and research enhances teaching. The perceived benefits of teaching on research provides a new insight into the research and teaching nexus from which the opportunity exists to foster these approaches and develop institutional policy to grow and sustain the research-teaching interactions. Highlights: Academic faculty reported that their teaching is enriched by research. Academic faculty placed a high value on students learning the competencies associated with research. Teaching and research were perceived to be two-way and mutually enhancing.